Kajian penentuan kawasan bukit berisiko menggunakan sistem maklumat geografi (GIS) - Harun, Norhazliana Ezreen (2006)
Development in the hill area contribute a hot issues in term of safety and environmental lately. As an option, a proper plan of development should be considered before carry on to develop the hill area. This study concentrates the usage of GIS as a tool to generate the maps of sensitive hill area in order to help planner identify the most suitable development area. The location of study is Majlis Pembandaran Ampang Jaya where all the inputs are taken care off in the database. All the input is then been analyze by using a software which known as Arc View 3.2 to produce a map off sensitive area which indicate 3 different indexes (low, medium and high). Hopefully this research will be very helpful to planner to identify the most suitable hill area to be developed.